PEMODELAN EKONOMETRIK DAN DINAMIKA SISTEM DAYA SAING EKSPOR KOMODITI AGROINDUSTRI KARET ALAM NDONESIA - Jono M. Munandar, Joko Purwono, Taufik Djatna dan Adhi Bagus Waskito (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTThe objective of this research was to study the export competitiveness of Indonesian natural rubber agroindustry commodity, namely SIR 20 by analyzing and identifying factors which influence the market. The study consists of econometric and system dynamic model. This model also helps to forecast export competitiveness in the futureThe results of econometric modeling indicated that the significant factors were technology advancement, degree of trade liberalization, wage rate, exchange rate, and percapita incomes of importing countries. Verification was done using face validity method that indicated the relationship between identified factors appropriety with estimated economic logic. The result of forecasts indicated that the export competitiveness would continue to grow for the next 10 years. Export competitiveness rate would remain increasing if there were improvements of the factors.Key words : econometric, system dynamic, natural rubber, agroindustry